how do i solve 2(3b - 7) = 4 by expanding brackets?

how do i solve 2(3b - 7) = 4 by expanding brackets?

Answers
6b-14 = 4 is now a linear equation which you can solve by balancing or inverse operation
javaid.aslam
04 April 2011
First to get rid of the brackets you must multiply everything outside the brackets by everything inside. So 2(3b-7) becomes 6b - 14.
javaid.aslam
04 April 2011
sorry 6b = 18!
javaid.aslam
04 April 2011
6b = 16 therefore b = 3
javaid.aslam
04 April 2011
Add an answer Cancel reply

Similar questions